2021
DOI: 10.3390/ma14247714
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microgrooves by Synchronous Hybrid Laser and Shaped Tube Electrochemical Milling

Abstract: The fabrication of deep microgrooves has become an issue that needs to be addressed with the introduction of difficult-to-cut materials and ever-increasing stringent quality requirements. However, both laser machining and electrochemical machining could not fulfill the requirements of high machining efficiency and precision with good surface quality. In this paper, laser and shaped tube electrochemical milling (Laser-STEM) were initially employed to fabricate microgrooves. The mechanisms of the Laser-STEM proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The electrochemical micro-milling model with high-speed rotating was established based on the finite element analysis method, and the change of workpiece surface profile was predicted by the simulation of the machining electric field. Yang et al [ 25 ] conducted theoretical and experimental research on the mechanism of laser and shaped-tube electrochemical milling (Laser-STEM). Through the experiment, it was found that the efficiency and precision of the special section tube micro-groove machining could be improved by using synchronous laser-assisted STEM.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical micro-milling model with high-speed rotating was established based on the finite element analysis method, and the change of workpiece surface profile was predicted by the simulation of the machining electric field. Yang et al [ 25 ] conducted theoretical and experimental research on the mechanism of laser and shaped-tube electrochemical milling (Laser-STEM). Through the experiment, it was found that the efficiency and precision of the special section tube micro-groove machining could be improved by using synchronous laser-assisted STEM.…”
Section: Introductionmentioning
confidence: 99%